1976
DOI: 10.5636/jgg.28.145
|View full text |Cite
|
Sign up to set email alerts
|

Crustal dilatancy and geomagnetic variations of short period.

Abstract: Electromagneticinduction in a two-dimensional conductor having a rectangular cross-section embedded in a less conductive half-space is studied. Supposing that such a system of conductors represents an electric model of a dilatant region in the earth's crust, an appreciable enhancement of the horizontal magnetic field is found over the portion of the earth's surface immediately above the higher conductivity region for a certain frequency range of the inducing field.The possibility of monitoring an underground d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Therefore we will not consider such sources here, although under special circumstances (e.g. the geometry of local conductivity changes) they may produce anomalies of substantial magnitude [Honkura and Kubo, 1986;Merzer and Klemperer, 1997;Rikitake, 1976aRikitake, , 1976b.…”
Section: Sources Of the Electromagnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we will not consider such sources here, although under special circumstances (e.g. the geometry of local conductivity changes) they may produce anomalies of substantial magnitude [Honkura and Kubo, 1986;Merzer and Klemperer, 1997;Rikitake, 1976aRikitake, , 1976b.…”
Section: Sources Of the Electromagnetic Fieldmentioning
confidence: 99%
“…Such phenomena have been discussed in several monographs and reviews [Gokhberg et al, 1995;Hayakawa and Fujinawa, 1994;Johnston, 1989Johnston, , 1997Lighthill, 1996;Park, 1996;Park et al, 1993;Rikitake, 1976aRikitake, , 1976b. We wish to describe briefly a scenario for them based on 1) analysis of experimental field and laboratory data and 2) modeling of electromagnetic emission which incorporates a mechanical model for pre-seismic deformation developed by us over the past fifteen years [Dobrovolsky et al, 1989;Gershenzon, 1992;Gershenzon and Gokhberg, 1989Gershenzon et al, 1986Gershenzon et al, , 1987Gershenzon et al, , 1989aGershenzon et al, , 1989bGershenzon et al, , 1990Grigoryev et al, 1989;Wolfe et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…However, the approximation of steady currents does not hold good and the theory described in this paper is no longer applicable. Electromagnetic induction must be fully taken into account as was discussed in detail by RIKITAKE (1976 …”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…RIKITAKE (1976) numerically investigated electromagnetic response in the crust with a resistivity anomaly as caused by dilatancy and suggested a possibility of detecting changes in the magnetic field observed on the earth's surface. In fact, changes in the ratio of the vertical to the horizontal components of geomagnetic variations have been reported to have taken place in association with the occurrence of earthquakes (YANAGIHARA, 1972;MIYA-KOSHI, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…This is in fact a difficult spectral range to record instrumentally. Rikitake (1976a) modelled electromagnetic induction in a 2-D rectangular conductor taken to represent a dilatant region in the Earth's crust. Using the appropriate induction parameters it was found that, for the particular model studied, enhancements of the horizontal field of up to 100% might be expected for short period (< 100 s) events.…”
Section: Frequency Contentmentioning
confidence: 99%